PENYELESAIAN MASALAH PENUGASAN PADA PENEMPATAN POSISI DENGAN ALGORITMA HUNGARIA - Chandra, Tintin (Jurnal TIMES, 2016)
In business always find out where an worker take many job and sometime one job do by many worker. Although job or employee depend the condition where area duty. If we talk about safety, maybe need more worker like fireman, policeman, soldiers, etc. If we talk position, so never one position have many worker to do the job like President, Vice President, Ministry, etc. So to make optimal we use Hungarian Method to help solve problem. Result of solution can be solve with same count worker with job or different count between worker with job. Algorithm Hungarian develop by Kuhn at based mathematical from another person such as Denes Konig and Jeno Egervary. Solution from Algortihm Hungarian expected to optimal cost with optimal job. So the company or firm can use this technic to solve or eliminate worker to pass the position with specialization or requirements skill to do the job.